Robótica educacional na formação continuada de professores: inovação nas práticas educativas da educação básica - Almansa, Filipi Michels (2021)
This study aims to analyze how inserting educational robotics (ER) into the continuing education of teachers enhances the innovation of educational practices. For this, two training cycles were organized with teachers from the municipal public educational network of Cachoeira do Sul - Rio Grande do Sul - enrolled in the schools covered by the Connected Education Innovation Program. This is a qualitative action study whose delimitation, organization, and data analysis were mediated by three cartographic matrices: the Dialogical-Problematizing Matrix, the Thematic-Organizing Matrix, and the Thematic-Analytical Matrix. The data were produced by using lesson plans, participant observation, and semi-structured interviews. Then, three categories were organized for analysis and discussion: Teachers’ perception of Educational Technology: the Need for Technological- Pedagogical Fluency (TPF) in the Teaching-Learning Process”; “Educational Robotics: Challenges and Potentialities in the Teaching-Learning process in basic education”; and “Public Educational Policies: Innovate to Democratize Teaching- Learning.”In the course of the study, ethical issues were observed regarding the privacy of the collaborators who consented to their participation. The theoretical foundation is based on the studies of Papert (1985), Tripp (2005), César (2013), Mallmann (2015), and D’Abreu (2018), among others. In view of this, it is understood that ER, when used in continuing education programs, enhances the innovation of educational practices in primary education. The productions developed during the training and shared as Open Educational Resources mobilize innovative practices by enabling access and adaptations, thereby democratizing the teaching-learning process.